On an ancient exile of light. The obliterated contacts between greek gnosis and M. Henry’s philosophy (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The philosophy of Michel Henry carried out a proposal of radicalization of phenomenology, which appeals to a foregrounding of affectivity as an expression of Life. In order to account for this turn, he proposed the opposing categories of Greek gnosis and Christian gnosis. The first one is associated with the commitment of describing the world in its exteriority and the second one is linked to the experience of the flesh. However, among the philosophies of Greek antiquity, the Cyrenaics raised many issues similar to those of the henryan treatment of affectivity. This work studies this relationship by reviewing the main aspects of the henryan characterization of Greek gnosis and then connects it with the key points of the Cyrenaic philosophy about affection, internal tact and the design of a language that reflects affectivity. This exploration will allow us to evaluate the scope of the thesis about the homogeneity of the Greek gnosis and will show important factors of the ancient thought about immanence.
Keywords: Phenomenology; Michel Henry; cyrenaics; self-affection; immanence